(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
Retail shopper’s behavior is an important area for market researchers. Behavior of consumers when purchasing retail consumer goods, predominantly food, beverages and household hygiene products result from the complementary work of a large number of different factors, including demographic, economic, geographical, social, psychological and situational factors. In order to implement the appropriate marketing strategy, it is necessary to conduct appropriate marketing research of consumers in the purchase of consumer goods and to analyze the influence of factors that dominantly influence the selection of retail chains for small purchases in Bosnia and Herzegovina. An exploratory (empirical) research, based on questionnaire survey research design, was conducted for identification of factors. The survey was conducted using the survey questionnaire on a representative sample of 350 respondents in the area of Sarajevo, Banja Luka and Mostar with the aim of determining the prevailing buying behavior of consumers making small purchases in Bosnia and Herzegovina. For the purpose of analyzing the collected data, the statistical package of SPSS was used, and in particular the method multivariate variance analysis (MANOVA). On the basis of the results obtained, the factors that have the greatest influence on the selection of stores for small purchases in Bosnia and Herzegovina at the level of Sarajevo, Banja Luka and Mostar can be determined.